A flexible sodium battery composite solid electrolyte and a preparation method and application thereof
Patent Information
- Application Number
- CN202610846382.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-12
- Publication Date
- 2026-10-30
AI Technical Summary
上述三项专利文献的技术方案均公开了无机电解质与聚合物电解质制备的复合固态电解质,但是制备的复合固态电解质的比容量性能仍有待进一步提升
[0035]本发明通过引发剂将有机物A、有机物B和有机物C聚合构建三维交联网络结构,该三维交联网络结构能够有效降低聚合物结晶度、扩大无定形区域,促进聚合物链段运动;同时添加无机填料制备复合固态电解质,进一步抑制了聚合物结晶,并提供了聚合物三维交联网络、有机-无机界面、无机电解质三条传输路径,从而显著降低钠离子传输势垒,提升复合电解质的室温离子电导率。含腈基有机物B赋予了复合固态电解质优异的本征高压稳定性;结合有机物A、有机物B、有机物C协同构建NaF/Na3N稳定界面,有效抑制了副反应与分解,电化学窗口显著拓宽,可稳定匹配低成本高压层状氧化物正极,利于高能量密度电池的实现。因此,基于该高性能复合固态电解质组装的固态钠电池,兼具高离子电导率与优异电化学稳定性,并能与低成本高压层状氧化物正极适配,展现出良好的产业化应用前景。
Smart Images

Figure CN123018092A_ABST
Abstract
Description
Technical Field
[0002] This invention belongs to the field of sodium metal battery solid electrolyte technology, specifically relating to a flexible sodium battery composite solid electrolyte, its preparation method, and its application. Background Technology
[0004] Global energy demand continues to grow, coupled with environmental pollution caused by fossil fuel combustion, driving the accelerated transformation and application of renewable energy sources such as wind and solar power. However, the inherent intermittent nature of these renewable energy sources makes it difficult to match energy supply with demand, thus making the development of large-scale, high-efficiency energy storage systems an urgent need. Sodium metal batteries, with their high theoretical specific capacity, low electrochemical potential, and abundant natural sodium resources, have become a highly promising energy storage system in this field. However, sodium metal batteries based on traditional liquid electrolytes still face many severe challenges in practical applications, including electrolyte leakage, thermal runaway, uncontrolled growth of sodium dendrites, and safety risks such as flammability and explosion.
[0005] In contrast, solid-state sodium metal batteries possess superior thermal stability, higher mechanical strength, and non-flammability. These advantages not only effectively suppress dendrite growth but also eliminate safety hazards caused by electrolyte leakage. Therefore, solid-state sodium metal batteries, with their inherent safety and strong commercial application potential, hold significant research value in the field of novel energy storage.
[0006] Currently, solid electrolytes for sodium metal batteries mainly include two types: inorganic solid electrolytes and polymer solid electrolytes. Inorganic solid electrolytes have high ionic conductivity and superior mechanical properties, but they suffer from poor interfacial contact with solid electrodes. The stress generated by electrode volume changes during cycling further exacerbates this problem, severely restricting the long-term cycle stability of the battery. In contrast, polymer solid electrolytes have a simple preparation process, good flexibility, and can improve interfacial contact with electrodes. However, their disadvantages are also significant, such as low ionic conductivity, limited mechanical strength, and insufficient stability at high operating voltages.
[0007] Composite solid electrolytes effectively integrate the advantages of two electrolyte materials by combining them. While maintaining the advantages of polymers such as simple preparation process, good interfacial compatibility, and flexibility, the added inorganic solid electrolyte components improve the sodium ion transport rate through different pathways, such as reducing the crystallinity of the polymer and providing additional sodium ion transport channels, and have broad application prospects.
[0008] The prior art patent document CN202410263514.X discloses a flexible composite solid electrolyte, its preparation method, and its application. The flexible composite solid electrolyte is prepared from the following raw materials in the following weight percentages: solute salt 5wt%~30wt%; inorganic filler 5wt%~80wt%; polymer substrate 10wt%~80wt%. The polymer substrate is composed of polymer A and compound B in a mass ratio of 1~10:1. Polymer A is one or more of polyether polyurethane or polyester polyurethane, and compound B is one or more of fluorinated polymers such as ethylene-tetrafluoroethylene copolymer, polytetrafluoroethylene, fluorinated ethylene-propylene copolymer, perfluoroalkoxy resin, polychlorotrifluoroethylene, ethylene-chlorotrifluoroethylene copolymer, polyvinylidene fluoride, polyvinylidene fluoride, or polyvinylidene fluoride-hexafluoropropylene. This flexible composite solid electrolyte has a high voltage window of 5.0V, and lithium iron phosphate / nickel-cobalt-manganese batteries assembled with high-voltage cathode materials exhibit high specific capacity and stable cycling performance. Patent document CN202411831335.8 discloses a thermoplastic polyurethane elastomer flexible composite solid electrolyte, its preparation method, and its application. This flexible composite solid electrolyte is prepared from the following raw materials in the following weight percentages: solute salt 1wt%~30wt%; inorganic filler 5wt%~50wt%; polymer matrix 40wt%~90wt%. The inorganic filler is one or more of active or inert fillers. The active filler is one or more of garnet-type fillers, perovskite-type materials, LISICON-type fillers, or NASICON-type fillers. The inert filler is one or more of natural clay, SiO2, or Al2O3. The polymer A is a polyether-based polyurethane, a polyester-based polyurethane, or a polyimide-based polyurethane. Compound B is one or more of urethane or polyurea-type polyurethane, and is one or more of polyethylene glycol diacrylate, pentaerythritol triacrylate, or isoprene tetraacrylate. Polymer A typically has excellent mechanical properties. The hard and soft segments constituting polymer A can provide mechanical properties and ion conduction properties, respectively. Therefore, using polymer A as the polymer matrix can prepare a flexible composite solid electrolyte with excellent mechanical properties. Compound B can undergo free radical polymerization to break the double bonds under external conditions, generating a polymer crosslinking network rich in ether oxygen groups, which can further enhance the ion transport efficiency inside the polymer matrix. The prepared composite solid electrolyte has both high flexibility and high ion conductivity, making it promising for application in wearable electronic devices.Patent document CN202511135155.0 discloses a thermoset sodium metal battery composite solid electrolyte, its preparation method, and its application. The composite solid electrolyte is prepared from the following raw materials in the following weight percentages: solute salt 1wt%~30wt%; inorganic filler 1wt%~50wt%; polymer matrix 50wt%~90wt%; initiator 0.5wt%~1wt%. This composite solid electrolyte exhibits good interfacial contact and stability, excellent mechanical properties, and high ionic conductivity, enabling sodium metal coin cells assembled based on this composite solid electrolyte to achieve stable cycling over a long lifespan. The technical solutions of the above three patent documents all disclose composite solid electrolytes prepared from inorganic and polymer electrolytes; however, the specific capacity performance of the prepared composite solid electrolytes still needs further improvement. Summary of the Invention
[0010] Addressing the shortcomings of traditional inorganic solid electrolytes and polymer solid electrolytes, and highlighting the promising prospects of composite solid electrolytes, this invention aims to provide a flexible sodium battery composite solid electrolyte and its preparation method. The composite solid electrolyte prepared by this method exhibits good interfacial contact, high ionic conductivity, and excellent electrochemical stability. This enables coin-type sodium metal batteries assembled based on this composite solid electrolyte to be compatible with low-cost, high-voltage layered oxide cathode materials, achieving higher battery energy density and making it a promising candidate for commercial application as a potential electrolyte.
[0011] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0012] A flexible sodium battery composite solid electrolyte, which is prepared from the following raw materials in the following weight percentages:
[0013] Solute salt 1wt%~30wt%;
[0014] Inorganic fillers 1wt%~50wt%;
[0015] Polymer matrix 50wt%~90wt%;
[0016] Initiator 0.5wt%~1wt%;
[0017] The polymer matrix is composed of organic compound A, organic compound B, and organic compound C in a mass ratio of 5~50:4:1, wherein organic compound A is one or more of methyl acrylate, ethyl acrylate, butyl acrylate, hexafluorobutyl acrylate, butyl methacrylate, or hexafluoromethyl acrylate; organic compound B is one or more of acrylonitrile, methacrylonitrile, or 2-chloroacrylonitrile; and organic compound C is one or more of acrylamide, N,N-methylenebisacrylamide, or N-methylacrylamide.
[0018] In the composite solid electrolyte of this invention, organic compounds A and C both possess ether oxygen and carbonyl functional groups that bind to sodium ions, enabling strong coordination with sodium ions and facilitating their transport along polymer chains, thus significantly promoting efficient sodium ion migration. Organic compounds A, B, and C crosslink and polymerize under the action of an initiator to form a stable three-dimensional crosslinked network. The addition of inorganic fillers reduces polymer crystallinity, increases the area of amorphous regions, and improves the speed of polymer chain movement, ultimately enhancing the room-temperature ionic conductivity of the polymer solid electrolyte and promoting sodium ion migration, providing excellent mechanical properties for the composite solid electrolyte. Organic compound B contains nitrile groups, exhibiting strong antioxidant capabilities and significantly improving the high-voltage stability of the composite electrolyte. The fluorine-rich functional groups of organic compound A, together with nitrogen-containing organic compounds B and C, form a robust NaF / Na3N interface layer on the sodium anode surface, significantly improving the contact between the electrolyte and the electrode and suppressing the decomposition tendency of the composite solid electrolyte membrane. The synergistic effect of the components in the composite solid electrolyte enhances the high-voltage oxidation resistance of the composite solid electrolyte membrane by improving its intrinsic antioxidant capacity and the protection of the artificial interface layer. This enables the composite solid electrolyte to be stably matched with low-cost high-voltage layered oxide cathodes, providing a feasible technical route for realizing high-energy-density solid sodium batteries.
[0019] Preferably, the composite solid electrolyte is prepared from the following raw materials in the following weight percentages: 10wt%~20wt% solute salt, 5wt%~50wt% inorganic filler, 0.5~1wt% initiator, and the balance being a polymer matrix.
[0020] Preferably, the solute salt is one or more of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium bis-trifluoromethanesulfonylimide (NaTFSI), sodium bis-fluorosulfonylimide (NaFSI), or sodium difluorooxalate borate (NaDFOB).
[0021] Preferably, the inorganic filler is Na3Zr2Si2PO4. 12 One or more of Na-Beta-Al2O3 or Na3PS4.
[0022] Preferably, the initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and tert-butyl hydroperoxide / sodium metabisulfite.
[0023] Preferably, the mass ratio of organic A, organic B and organic C in the polymer matrix is 20:4:1.
[0024] A method for preparing a flexible sodium battery composite solid electrolyte, the specific preparation steps of which are as follows:
[0025] Step S1: Dissolve organic compounds A, B, and C in solvent D, and heat and stir until completely dissolved to obtain mixed solution E;
[0026] Step S2: Add the solute salt and initiator to the mixed solution E obtained in step S1, and stir until the mixture is homogeneous to obtain a mixed slurry;
[0027] Step S3: Add the inorganic filler to solvent D, and ultrasonically disperse and stir until uniform to obtain an inorganic filler suspension;
[0028] Step S4: Add the inorganic filler suspension obtained in step S3 to the mixed slurry E obtained in step S2, and stir until it is evenly dispersed to obtain a mixed slurry;
[0029] Step S5: The mixed slurry obtained in step S4 is cast onto a glass plate, heated to initiate polymerization, and then dried and cured before being removed to finally obtain the flexible sodium battery composite solid electrolyte.
[0030] Preferably, the solvent D in step S1 is one or more of ethylene glycol dimethyl ether, N-methylpyrrolidone, dimethyl sulfoxide, or N,N-dimethylformamide.
[0031] Preferably, the heating and stirring in steps S1 to S4 are carried out in a magnetic stirring oil bath, and the heating and stirring temperature is 30~120 ℃.
[0032] A sodium battery is assembled into a coin cell using the aforementioned composite solid electrolyte, a layered oxide cathode, and sodium metal.
[0033] Preferably, the NNFM||Na coin cell assembled with the above-mentioned composite solid electrolyte, layered oxide cathode and sodium metal can stably cycle for 150 cycles at 0.2 C and 30 ℃, with a discharge specific capacity of 125.2 mAh / g in the first cycle and 100.4 mAh / g after 150 cycles, and a capacity retention rate of 80.2%.
[0034] Compared with the prior art, the present invention has the following advantages and beneficial effects:
[0035] This invention utilizes an initiator to polymerize organic compounds A, B, and C to construct a three-dimensional cross-linked network structure. This three-dimensional cross-linked network structure effectively reduces polymer crystallinity, expands the amorphous region, and promotes polymer chain segment movement. Simultaneously, the addition of inorganic fillers to prepare a composite solid electrolyte further inhibits polymer crystallization and provides three transport pathways: the polymer three-dimensional cross-linked network, the organic-inorganic interface, and the inorganic electrolyte. This significantly reduces the sodium ion transport barrier and improves the room-temperature ionic conductivity of the composite electrolyte. The nitrile-containing organic compound B endows the composite solid electrolyte with excellent intrinsic high-voltage stability. The synergistic construction of the NaF / Na3N stable interface by organic compounds A, B, and C effectively suppresses side reactions and decomposition, significantly widening the electrochemical window. This allows for stable matching with low-cost, high-voltage layered oxide cathodes, facilitating the realization of high-energy-density batteries. Therefore, the solid-state sodium battery assembled based on this high-performance composite solid electrolyte possesses both high ionic conductivity and excellent electrochemical stability, and is compatible with low-cost, high-voltage layered oxide cathodes, demonstrating promising prospects for industrial application. Attached Figure Description
[0037] Figure 1 The electrochemical impedance spectroscopy diagrams are for the composite solid electrolytes prepared in Example 1, Comparative Example 1, and Comparative Example 2.
[0038] Figure 2 The electrochemical window of the composite solid electrolyte prepared in Example 1, Comparative Example 1, and Comparative Example 2.
[0039] Figure 3 The composite solid electrolytes prepared in Example 1, Comparative Examples 1 and 2 were applied in a Na||Na symmetric battery system with a performance of 0.1~2.0 mA / cm². 2 The critical current density curve below.
[0040] Figure 4 Cycling curves of the composite solid electrolyte prepared in Example 1 in the (sodium nickel iron manganese) NNFM||Na battery system under conditions of 2.0~4.1V, 0.2C, and 30℃. Detailed Implementation
[0042] The following detailed description of the present invention, with reference to the accompanying drawings and specific embodiments, should not be construed as limiting the scope of the subject matter of the present invention to the following embodiments. All technologies implemented based on the above content of the present invention fall within the scope of the present invention.
[0043] Example 1
[0044] 1.00 g of hexafluorobutyl acrylate was added to 6 mL of DMSO solvent. After isolating from air, the solution was placed on a magnetic stirrer and stirred for 30 min at 60 ℃ and 900 r / min until the hexafluorobutyl acrylate was completely dissolved. Then, 0.20 g of acrylonitrile (AN) and 0.05 g of acrylamide (AM) were added, and the mixture was stirred for 30 min at 30 ℃ and 900 r / min until completely dissolved and evenly dispersed. Next, 0.20 g of solute salt NaClO4 was added, and the mixture was stirred until dissolved and evenly dispersed. Then, 0.01 g of azobisisobutyronitrile (AIBN) was added, and the mixture was stirred until evenly dispersed. The mixture was then heated and stirred for 1 h to obtain a viscous HFBA-AN-AM crosslinked polymer dispersed in DMSO. 20 wt% of the total mass of the composite solid electrolyte was weighed from the inorganic filler Na3Zr2Si2PO4. 12 Add the inorganic filler to 4 mL of DMSO, sonicate for 60 min, and then stir for 30 min at 900 r / min to ensure uniform dispersion. Add the inorganic filler suspension to the DMSO mixture of HFBA-AM-AN crosslinked polymer, and stir for 60 min at 30 ℃ and 900 r / min to obtain a uniformly dispersed solid electrolyte mixture. Let the solid electrolyte mixture stand for 6 h to remove air bubbles, then cast it onto a glass plate and dry it at 80 ℃ under vacuum for 24 h to obtain a composite solid electrolyte membrane.
[0045] The prepared composite solid electrolyte membrane was cut into 16 mm solid electrolyte discs using a slicer and assembled in a glove box into Na||stainless steel, NNFM||Na, Na|| layered oxide coin cells (CR2032 mold) for subsequent testing.
[0046] Example 2
[0047] The preparation method in this embodiment is the same as in Example 1, except that: the mass of hexafluorobutyl acrylate is replaced by 2.00 g instead of 1.00 g, the solute salt sodium perchlorate is replaced by sodium hexafluorophosphate, and the inorganic filler is Na3Zr2Si2PO4. 12 The mass percentage of 20wt% was replaced with 5wt%, the initiator was replaced with azobisisobutyronitrile (AIOBR) and the solvent DMSO was replaced with N-methylpyrrolidone (N-Methylpyrrolidone).
[0048] Example 3
[0049] The preparation method in this embodiment is the same as that in Example 1, except that the solute salt sodium perchlorate is replaced with sodium bis-trifluoromethanesulfonylimide, and the inorganic filler is Na3Zr2Si2PO4. 12The mass percentage of 20wt% is replaced with 10wt%, the initiator is replaced with dimethyl azobisisobutyrate instead of azobisisobutyronitrile, and the solvent DMSO is replaced with N,N-dimethylformamide.
[0050] Example 4
[0051] The preparation method in this embodiment is the same as in Example 1, except that the solute salt sodium perchlorate is replaced with sodium difluorosulfonyl imide, and the inorganic filler is Na3Zr2Si2PO4. 12 The mass percentage of 20wt% was replaced with 35wt%, the initiator was replaced with tert-butyl hydroperoxide / sodium metabisulfite, and the solvent DMSO was replaced with ethylene glycol dimethyl ether.
[0052] Example 5
[0053] The preparation method in this embodiment is the same as that in Example 1, except that the solute salt sodium perchlorate is replaced with sodium difluorooxalate borate, and the inorganic filler is Na3Zr2Si2PO4. 12 The mass percentage of 20wt% is replaced with 50wt%.
[0054] Comparative Example 1
[0055] Weigh 1.00 g of hexafluorobutyl acrylate and 0.20 g of acrylonitrile and add them to 6 mL of DMSO solvent. After isolating from air, place the solution on a magnetic stirrer and stir for 30 min at 60 ℃ and 900 r / min until the hexafluorobutyl acrylate is completely dissolved. Then add 0.20 g of solute salt NaClO4 and stir until dissolved and uniformly dispersed. Next, add 0.01 g of azobisisobutyronitrile (AIBN) and stir until uniformly dispersed. Heat and stir for another 1 h to obtain a viscous cross-linked polymer dispersed in DMSO. Weigh 20 wt% of the total mass of the composite solid electrolyte containing inorganic filler Na3Zr2Si2PO4. 12 Add the inorganic filler to 4 mL of DMSO, sonicate for 60 min, and then stir for 30 min at 900 r / min to ensure uniform dispersion. Add the inorganic filler suspension to the crosslinked polymer DMSO mixture and stir for 60 min at 30 ℃ and 900 r / min to obtain a uniformly dispersed solid electrolyte mixture. Let the electrolyte mixture stand for 6 h to remove air bubbles, then cast it onto a glass plate and dry it at 80 ℃ under vacuum for 24 h to obtain a composite solid electrolyte membrane.
[0056] The prepared composite solid electrolyte membrane was cut into 16 mm solid electrolyte discs using a slicer and assembled in a glove box into Na||stainless steel, NNFM||Na, Na|| layered oxide coin cells (CR2032 mold) for subsequent testing.
[0057] Comparative Example 2
[0058] Weigh 1.00 g of hexafluorobutyl acrylate and 0.05 g of acrylamide and add them to 6 mL of DMSO solvent. After isolating from air, place the solution on a magnetic stirrer and stir for 30 min at 60 ℃ and 900 r / min until the hexafluorobutyl acrylate is completely dissolved. Then add 0.20 g of solute salt NaClO4 and stir until dissolved and uniformly dispersed. Next, add 0.01 g of azobisisobutyronitrile (AIBN) and stir until uniformly dispersed. Heat and stir for another 1 h to obtain a viscous cross-linked polymer dispersed in DMSO. Weigh 20 wt% of the total mass of the composite solid electrolyte containing inorganic filler Na3Zr2Si2PO4. 12 Add the inorganic filler to 4 mL of DMSO, sonicate for 60 min, and then stir for 30 min at 900 r / min to ensure uniform dispersion. Add the inorganic filler suspension to the crosslinked polymer DMSO mixture and stir for 60 min at 30 ℃ and 900 r / min to obtain a uniformly dispersed solid electrolyte mixture. Let the electrolyte mixture stand for 6 h to remove air bubbles, then cast it onto a glass plate and dry it at 80 ℃ under vacuum for 24 h to obtain a composite solid electrolyte membrane.
[0059] The prepared composite solid electrolyte membrane was cut into 16 mm solid electrolyte discs using a slicer and assembled into Na||stainless steel, NNFM||Na coin cells (CR2032 mold) in a glove box for subsequent testing.
[0060] 1. Testing Method
[0061] (1) The composite solid electrolyte obtained from Example 1 and Comparative Example 1 and Comparative Example 2 were used to assemble stainless steel || stainless steel symmetrical coin cells. Electrochemical impedance was tested to analyze their charge transfer resistance and to calculate the ionic conductivity in combination with the electrolyte thickness and area.
[0062] (2) The composite solid electrolytes obtained from Example 1 and Comparative Examples 1 and 2 were used to assemble Na|| stainless steel coin cells, which were then subjected to LSV testing at a Metrohm workstation in Switzerland.
[0063] (3) The composite solid electrolyte obtained in Example 1 was assembled into a Na||Na coin cell and its critical current density performance was tested in the LANDdt test software.
[0064] (4) The composite solid electrolyte obtained in Example 1 was assembled into an NNFM||Na coin cell and subjected to constant current charge-discharge test at a rate of 0.2 C (0.1 C = 133 mAh / g) using LANDdt test software.
[0065] 2. Test Results
[0066] like Figure 1 As shown, the composite solid electrolyte prepared in Example 1 has the lowest bulk resistance, and its ionic conductivity can be calculated using the following formula:
[0067]
[0068] Where: σ is the ionic conductivity, in mS / cm; L is the material thickness, in cm; R... b S is the bulk resistance, in Ω, and S is the contact area, in cm². 2 The calculated ionic conductivity of the composite solid electrolyte prepared in Example 1 was 0.32 mS / cm, which is higher than that of the composite solid electrolyte prepared in Comparative Example 1 (0.20 mS / cm) and Comparative Example 2 (0.24 mS / cm).
[0069] like Figure 2 As shown in the figure, the composite solid electrolyte obtained in Example 1 has an oxidation resistance voltage of approximately 4.78 V. The wider electrochemical window allows the example to exhibit more stable electrochemical performance, which helps to reduce the battery aging rate and extend its service life.
[0070] like Figure 3 As shown, after assembling the composite solid electrolyte obtained in Example 1 into a Na||Na coin cell, a current of 1.7 mA / cm² was achieved in the deposition-stripping cycle test with gradually increasing current. 2 The critical current density is higher than 1.0 mA / cm² for Comparative Examples 1 and 2. 2 0.7 mA / cm 2 This demonstrates that the composite solid electrolyte prepared in Example 1 has superior sodium uniform deposition / stripping ability and stronger high current resistance, effectively suppresses sodium dendrite growth, and exhibits better interface stability and electrochemical reversibility.
[0071] like Figure 4 As shown, after assembling the composite solid electrolyte obtained in Example 1 into an NNFM||Na coin cell, it can be stably cycled for 150 cycles under the conditions of 2.0-4.1V, 0.2C, and 30℃. The discharge specific capacity of the first cycle is 125.2 mAh / g, and the discharge specific capacity after 150 cycles is 100.4 mAh / g, with a capacity retention rate of 80.2%.
[0072] The above embodiments describe the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are only illustrative of the principles of the present invention. Various changes and modifications can be made to the present invention without departing from the scope of the principles of the present invention, and all such changes and modifications fall within the protection scope of the present invention.
Claims
1. A flexible sodium battery composite solid electrolyte, characterized in that... The composite solid electrolyte is prepared from the following raw materials in the following weight percentages: Solute salt 1wt%~30wt%; Inorganic fillers 1wt%~50wt%; Polymer matrix 50wt%~90wt%; Initiator 0.5wt%~1wt%; The polymer matrix is composed of organic A, organic B, and organic C in a mass ratio of 5~50:4:
1. Organic A is one or more of methyl acrylate, ethyl acrylate, butyl acrylate, hexafluorobutyl acrylate, butyl methacrylate, or hexafluoromethyl acrylate; organic B is one or more of acrylonitrile, methacrylonitrile, or 2-chloroacrylonitrile; and organic C is one or more of acrylamide, N,N-methylenebisacrylamide, or N-methacrylamide. Organic B contains nitrile groups, which have strong antioxidant capacity and can significantly improve the high-voltage stability of the composite electrolyte. The fluorine-rich functional groups of organic A, together with nitrogen-containing organic B and organic C, form a robust NaF / Na3N interface layer on the sodium negative electrode surface, which significantly improves the contact between the electrolyte and the electrode and inhibits the decomposition tendency of the composite solid electrolyte membrane.
2. The flexible sodium battery composite solid electrolyte according to claim 1, characterized in that... The composite solid electrolyte is prepared from the following raw materials in the following weight percentages: 10wt%~20wt% solute salt, 5wt%~50wt% inorganic filler, 0.5~1wt% initiator, and the balance being polymer matrix.
3. The flexible sodium battery composite solid electrolyte according to claim 1, characterized in that: The solute salt is one or more of sodium hexafluorophosphate (NaPF6), sodium perchlorate (NaClO4), sodium bis-trifluoromethanesulfonylimide (NaTFSI), sodium bis-fluorosulfonylimide (NaFSI), or sodium difluorooxalate borate (NaDFOB).
4. The flexible sodium battery composite solid electrolyte according to claim 1, characterized in that: The inorganic filler is Na3Zr2Si2PO4. 12 One or more of Na-Beta-Al2O3 or Na3PS4.
5. The flexible sodium battery composite solid electrolyte according to claim 1, characterized in that: The initiator is one or more of azobisisobutyronitrile, azobisisoheptanenitrile, dimethyl azobisisobutyrate, and tert-butyl hydroperoxide / sodium metabisulfite.
6. A method for preparing a flexible sodium battery composite solid electrolyte according to any one of claims 1 to 5, characterized in that... The specific preparation steps are as follows: Step S1: Dissolve organic compounds A, B, and C in solvent D, and heat and stir until completely dissolved to obtain mixed solution E; Step S2: Add the solute salt and initiator to the mixed solution E obtained in step S1, and stir until the mixture is homogeneous to obtain a mixed slurry; Step S3: Add the inorganic filler to solvent D, and ultrasonically disperse and stir until uniform to obtain an inorganic filler suspension; Step S4: Add the inorganic filler suspension obtained in step S3 to the mixed slurry E obtained in step S2, and stir until it is evenly dispersed to obtain a mixed slurry; Step S5: The mixed slurry obtained in step S4 is cast onto a glass plate, heated to initiate polymerization, and then dried and cured before being removed to finally obtain the flexible sodium battery composite solid electrolyte.
7. The method for preparing the flexible sodium battery composite solid electrolyte according to claim 6, characterized in that: The solvent D mentioned in step S1 is one or more of ethylene glycol dimethyl ether, N-methylpyrrolidone, dimethyl sulfoxide, or N,N-dimethylformamide.
8. The method for preparing the flexible sodium battery composite solid electrolyte according to claim 6, characterized in that: In steps S1 to S4, heating and stirring are carried out in a magnetic stirring oil bath, and the heating and stirring temperature is 30~120 ℃.
9. A sodium battery, characterized in that: A coin cell sodium battery is assembled using the composite solid electrolyte as described in any one of claims 1 to 5, a layered oxide cathode, and sodium metal.
10. The sodium battery according to claim 9, characterized in that: The NNFM||Na coin cell, assembled with the composite solid electrolyte as described in any one of claims 1 to 5, a layered oxide cathode, and sodium metal, can stably cycle for 150 cycles at 0.2 C and 30 ℃. The discharge specific capacity of the first cycle is 125.2 mAh / g, and the discharge specific capacity after 150 cycles is 100.4 mAh / g, with a capacity retention rate of 80.2%.
Citation Information
Patent Citations
Flexible composite solid electrolyte and preparation and application thereof
CN117855582A
Thermoplastic polyurethane elastomer flexible composite solid electrolyte as well as preparation method and application thereof
CN119542524A
Composite solid electrolyte of thermosetting sodium metal battery as well as preparation method and application of composite solid electrolyte
CN120978188A
